English Teachers’ Responses on the Indonesian MOOC: Technology for Autonomous Learning (A Qualitative Survey at Central Java Province, Indonesia) - Hartono, Rudi (Language Circle: Journal of Language and Literature, 2017)
The birth and existence of Indonesian Massive Open Online Course (IMOOC) facilitate English teachers in Indonesia to improve their English teaching skills and explore various potential digital tools to help promote autonomous learning in their language classrooms. To prove this fact I did a qualitative survey on 17 English teachers as the IMOOC participants from Central Java. I gave them questionnaires through a Google Form. By using this data collection technique I got their responses on the importance and advantage of the Indonesian MOOC as Technology for Autonomous Learning in their English classroom context and situation. Based on the survey data, it was known that the participants: 1) had not followed MOOCs (60%), 2) did not know the advantages of MOOC (70%), 3) knew IMOOC (86%), 4) were interested in following IMOOC (100%), 5) became autonomous learners (90%), 6) were upgrading their ICT competence for English teaching (100%), 7) were improving their career as English teachers (100%). From this survey, I have much invaluable information to map the role and function of the Indonesian MOOC for English teaching and learning autonomously. The Indonesian MOOC is really significant for English teachers to face a global era, especially for their digital literacy competence.